Position Control of DC Motor Using PID and LQR Methods: A Comparative Analysis - Ivan Nanda Septiandi; Salsabila Ika Yuniza (Journal of Marine Electrical and Electronic Technology, 2024)
The rapid technological advancements of this era have significantly influenced various fields, including engineering and innovation in electrical systems. Accessing and utilizing technological knowledge has become increasingly convenient, enabling researchers and engineers to push boundaries in innovation and development. In the field of electrical engineering, this ease of access has facilitated the study and implementation of advanced techniques for efficient energy utilization and control systems. For instance, the exploration of DC motor control methodologies, such as PID and LQR, highlights the potential for optimizing performance in industrial and robotic applications. Research and testing play a pivotal role in driving future innovations by ensuring that electrical systems meet the growing demands for power efficiency and technological sophistication. This study specifically addresses the development and analysis of DC motor position control using PID and LQR methods, providing a comparative evaluation of their performance metrics. These findings contribute to the advancement of robust and efficient control systems, aligning with the needs of modern engineering applications.